(untitled) (Bangladesh Journal of Pharmacology, 2013)
The present study was undertaken to investigate the protective effect of hydroalcoholic extract of leaves of Ipomoea staphylina against carbon tertrachloride- and gentamicin-induce hepatotoxicity and nephrotoxicity in rats respectively. The extract (200 mg/kg, p.o) showed hepatoprotective activity against carbon tetrachloride-induced hepatotoxicity by significantly (p<0.001) reducing the levels of AST, ALT, ALP, total bilirubin and significantly (p<0.001) increasing the serum total protein. The extract also showed nephro-protective activity against gentamicin-induced nephrotoxicity by significantly (p<0.001) reducing the levels of blood urea, blood urea nitrogen (BUN), serum creatinine and significantly (p<0.001) increasing the serum total protein. The extract also improves the histology of the liver and kidney. The total phenolic content and the total flavonoid content of the extract were 94.59 ± 2.54 mg gallic acid equivalent/g and 44.68 ± 2.00 mg rutin equivalent/g respectively.